PENGARUH MODEL PEMBELAJARAN INQUIRY DALAM MENULIS TEKS PROSEDUR KOMPLEKS PADA SISWA KELAS XI - Novia Andriani; Nirmawan Nirmawan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Indonesian language learning is to improve students’ ability to understand, analyze, evaluate, and produce. This is the background of the researcher to examine the effect of the inquiry learning model on the lesson of writing complex procedure texts. This study aims to improve students’ ability to write complex procedural texts using the inquiry learning model in class XI SMA Muhammadiyah 1 Medan for the 2020-2021 academic year. The population of this study is all students of class XI, totaling 103 students using a sample of 40 students with random sampling, the method used in this study is an experimental method with a two group pre-test and post-test design. The instrument used to test the ability to write complex procedure texts. The average value of ability in writing complex procedure texts before using the inquiry model is 72,1 while the average value of ability in writing complex procedure texts after using the inquiry model is 80,25. Based on the results of the pre-test and post-test class correlation analysis conducted with the product moment correlation formula, it obtained an r value of 0,965 so that thitung 22,456 >ttabel 2,021, it was concluded that the inquiry model had a significant influence on the ability to write complex procedure texts in class XI high school students SMA Muhammadiyah 1 Medan Academic Year 2020-2021.